Understanding How School Climate Affects Overall Mood in Residential Care: Perspectives of Adolescent Girls in Foster Care and Juvenile Justice Systems. (1st December 2018) - Somers, Cheryl L.; Day, Angelique G.; Niewiadomski, Jenna; Sutter, Casey; Baroni, Beverly A.; Hong, Jun Sung
Abstract: The aim of the study is to understand the perceptions of court‐involved adolescent girls in residential treatment (40% delinquency, 60% foster care/child abuse and neglect) on school climate and factors that affect their mood in school. Participants included 27 adolescent females in residential care for both types of court involvement in a large urban area in a Midwestern state. Age of the participants ranged from 12 to 18. Four major themes from the three focus groups that were conducted included relationships and interactions with peers, interactions with staff and teachers and their perceptions about these interactions, the demands of the learning environment, and sensitivity to being touched. Practice implications are discussed.